2013
DOI: 10.1103/physreve.87.012702
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion processes: Short-range correlations induced by adhesion and contact interactions

Abstract: We analyze the out-of-equilibrium behavior of exclusion processes where agents interact with their nearest neighbors, and we study the short-range correlations which develop because of the exclusion and other contact interactions. The form of interactions we focus on, including adhesion and contact-preserving interactions, is especially relevant for migration processes of living cells. We show the local agent density and nearest-neighbor two-point correlations resulting from simulations on two dimensional latt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 94 publications
(183 reference statements)
0
12
0
Order By: Relevance
“…Fernando's analysis showed that each of the very different adhesive collective migration mechanisms gave rise to a nonlinear diffusion equation, and they presented an extensive list of the different nonlinear diffusivity functions for each discrete mechanism [14]. Since these initial investigations, others have also considered different aspects of modeling adhesive collective migration processes in a lattice-based framework [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Fernando's analysis showed that each of the very different adhesive collective migration mechanisms gave rise to a nonlinear diffusion equation, and they presented an extensive list of the different nonlinear diffusivity functions for each discrete mechanism [14]. Since these initial investigations, others have also considered different aspects of modeling adhesive collective migration processes in a lattice-based framework [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…An area of great interest to the mathematical biology community is to understand how the averaged properties of a particular discrete process can be described using continous models such as ordinary differential equations and partial differential equations [30,20,1,[40][41][42]. While some previous work has been completed on understanding how to derive approximate differential equation description of systems with different sized agents [43,44], none of these previous studies considered systems that were composed of several types of different sized agents like we have shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Most models used to interpret two-dimensional tissue growth experiments do not apply to our experimental data. Standard continuous models neglect to account for individual-level properties, and standard discrete models assume that the size of the agents does not change dynamically [30,36,37,27,38,39,34,31,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations